Strategi Penerapan Nilai-nilai Islam Dalam Kehidupan Sehari-hari Untuk Meningkatkan Karakter Siswa - Maisarah (Fakultas Agama Islam Universitas Kutai Kartanegara Tenggarong, 2025)
The application of Islamic values in daily life plays a crucial role in shaping students' noble character, morality, and sense of responsibility. This study aims to identify effective strategies for integrating Islamic values into students' lives as part of character education. The methods used include literature review and observation of program implementation in Islamic-based school environments. The findings reveal that effective strategies include (1) habituation of daily worship practices, such as congregational prayers, Quran recitation, and dzikir; (2) strengthening Islamic values through an integrated curriculum; (3) fostering a conducive school environment through exemplary behavior of teachers and staff. The implementation of these strategies has proven effective in enhancing students' character, particularly in aspects of honesty, discipline, responsibility, and empathy for others. Thus, the application of Islamic values serves not only as the foundation for spiritual education but also as a basis for developing excellent and competitive character.